A Pure Rotational Spectroscopic Study of Two Nearly-Equivalent Structures of Hexafluoroacetone Imine, (CF3)C=NH - Daniel A. Obenchain; Beppo Hartwig; Daniel J. Frohman; G. S. Grubbs; B. E. Long; Wallace C. Pringle; Stewart E. Novick; S. A. Cooke (Molecules)
Rotational spectra for hexafluoroacetone imine, the singly substituted 13C isotopologues, and the 15N isotopologue, have been recorded using both cavity and chirped pulse Fourier transform microwave spectrometers. The spectra observed present as being doubled with separations between each pair of transitions being on the order of a few tens of kilohertz which is consistent with a large amplitude motion producing two torsional substates. The observed splitting is most likely due to the combined motions of the CF3 groups, for which the calculated barrier is small. However, no transitions between states could be observed and, similarly, no Coriolis coupling parameters were required to achieve a satisfactory fit for the transition frequencies. Hence, and somewhat curiously, the two states have been fit independently of each other such that the two states may simply be considered near-equivalent conformers. The structural properties of hexafluoroacetone imine are compared with two isoelectronic molecules hexafluoroisobutene and hexafluoroacetone. Rotational constants, quartic centrifugal distortion constants, and the 14N nuclear electric quadrupole coupling tensor have been determined and are presented together with supporting quantum chemical calculations.